Assessment on the Use of High Capacity "Sn4P3"/NHC Composite Electrodes for Sodium‐Ion Batteries with Ether and Carbonate Electrolytes. (20th August 2020) - Palaniselvam, Thangavelu; Mukundan, Charan; Hasa, Ivana; Santhosha, Aggunda L.; Goktas, Mustafa; Moon, Hyein; Ruttert, Mirco; Schmuch, Richard; Pollok, Kilian; Langenhorst, Falko; Winter, Martin; Passerini, Stefano; et al.
Abstract: This work reports the facile synthesis of a Sn–P composite combined with nitrogen doped hard carbon (NHC) obtained by ball‐milling and its use as electrode material for sodium ion batteries (SIBs). The "Sn4 P3 "/NHC electrode (with nominal composition "Sn4 P3 ":NHC = 75:25 wt%) when coupled with a diglyme‐based electrolyte rather than the most commonly employed carbonate‐based systems, exhibits a reversible capacity of 550 mAh gelectrode −1 at 50 mA g −1 and 440 mAh gelectrode −1 over 500 cycles (83% capacity retention). Morphology and solid electrolyte interphase formation of cycled "Sn4 P3 "/NHC electrodes is studied via electron microscopy and X‐ray photoelectron spectroscopy. The expansion of the electrode upon sodiation (300 mAh gelectrode −1 ) is only about 12–14% as determined by in situ electrochemical dilatometry, giving a reasonable explanation for the excellent cycle life despite the conversion‐type storage mechanism. In situ X‐ray diffraction shows that the discharge product is Na15 Sn4 . The formation of mostly amorphous Na3 P is derived from the overall (electro)chemical reactions. Upon charge the formation of Sn is observed while amorphous P is derived, which are reversibly alloying with Na in the subsequent cycles. However, the formation of Sn4 P3 can be certainly excluded. Abstract : Tin phosphide composited with nitrogen‐doped hard carbon is studied as the negative electrode for sodium ion batteries. The in situ X‐ray diffraction measurements reveal the differences in the storage behavior of tin phosphide in ether and carbonate electrolytes. The in situ electrochemical dilatometry study shows the active role of carbon to diminish the large volume expansion of tin phosphide during the (de)sodiation process.